Inside Back Cover: 2′β‐Fluoro‐Tricyclo Nucleic Acids (2′F‐tc‐ANA): Thermal Duplex Stability, Structural Studies, and RNase H Activation (Chem. Eur. J. 43/2017). Issue 43 (20th June 2017) - Istrate, Alena; Katolik, Adam; Istrate, Andrei; Leumann, Christian J.
Abstract : What a difference a fluorine makes when introduced into the 2′‐β‐position of the tricyclo‐DNA skeleton (2′F‐tc‐ANA). It steers the conformation of the furanose unit into an eastern conformation. Fully modified 2′F‐tc‐ANA shows enhanced binding to complementary RNA in the same way as parent tc‐DNA. Embedded in a 2′OMe‐RNA hybrid construct it enables RNaseH cleavage of a complementary RNA target, thus enhancing the application range of the tc‐DNA family as antisense agents. More information can be found in the Full Paper by C. J. Leumann et al. onpage 10310 .